Application of Symposium Discussion Method to Improve Students' Learning Outcomes: Action Research at State Senior High School 1 Suliki - Anto, Yuli (MANDAILING GLOBAL EDUKASIA, 2024)
This study aims to improve student learning outcomes in Islamic religious education learning using the Symposium Discussion Method. This study uses a type of classroom action research. The design of this study uses the Kemmis & Mctaggart design with four steps, namely planning, action, observation and reflection. The subjects of this study were elementary school students. Data were obtained using test and observation techniques. The data obtained were then analyzed using descriptive statistical techniques. The results of the study indicate that the Symposium Discussion Method can improve student learning outcomes in Islamic religious education learning. This can be seen in cycle I with an average percentage of 50% and in cycle II by 86%. So it can be stated that student learning outcomes have developed in cycle II. Improving student learning outcomes through the application of the Symposium Discussion Method in Islamic education learning is carried out for two cycles. Learning outcomes in cycle I were 66.67% and in cycle II by 76.67%. So it can be said that student learning outcomes improved better in cycle II. Based on this, the Symposium Discussion Method can be used as one of the media that can be considered by teachers to overcome the problem of low student learning outcomes in Islamic religious education learning.